Flora D’laman Enterprise / Mohamad Faisal Abdul Hamid ... [et al.] - Abdul Hamid, Mohamad Faisal; Mohamed Hashim, Mohd Fadzril; Mohamed, Abd Hadi; Mohd Saad, Mohd Faizal (2007)
Flora D’laman Enterprise will be registered as a Bumiputra Landscaping Company to carry out our philosophy to be in partnership with Mother Nature. We aim to register Flora D’laman Enterprise with the Pusat Khidmat Kontraktor (PKK) under Class E, Lembaga Pembangunan Industri Pembinaan Malaysia (CIDB) under Gred G3 and Kementerian Kewangan Malaysia. Flora D’laman Enterprise will be specializing in Soft and Hard Landscape projects within Perlis State over the years especially in our various endeavors in variety of project, we will gain valuable knowledges and experiences. Thus, we target that Flora D’laman Enterprise will expand its expertise to outside Perlis state, to be involved and become part of the booming economic in other state. We inspire to be the niche in the development and construction especially in landscaping business.